Characterizing mothers and children at risk of being under-immunized in India: A latent class analysis approach. (November 2020) - Holroyd, Taylor A.; Wahl, Brian; Gupta, Madhu; Sauer, Molly; Blunt, Madeleine; Gerste, Amelia K.; Erchick, Daniel J.; Santosham, Mathuram; Limaye, Rupali J.
Highlights: Immunization inequities persist in India despite substantial gains. Sociodemographic characteristics contribute to non-immunization or under-immunization. Tailored interventions can improve immunization coverage for those at high risk. Abstract: Objectives: While India has made substantial progress in introducing new vaccines and scaling up immunization coverage, inequities persist sub-nationally. This study was performed to investigate the risk of under-immunization based on class membership and to identify heterogeneous classes based on sociodemographic characteristics in pediatric and maternal populations in India through latent class analysis. Methods: Data from the most recent National Family Health Survey conducted in 2015–2016 were used. Latent class analysis was used to model immunization coverage in children aged 12–23 months and mothers, and to identify subgroups to characterize those at risk of not being immunized. Results: Patterns of sociodemographic characteristics were found to contribute to non-immunization or under-immunization among pediatric and maternal populations in India. Individuals who fit into one of three categories were identified in both populations: those at high, medium, and lower risk of not being immunized. Lower socioeconomic status, lack of antenatal care, and lower maternal education put individuals at higher risk of not being immunized with routine childhood vaccines and maternal tetanus toxoid. Conclusions: Predisposing risk factors can persistently impact immunization status despite improvements in immunization access in India. Tailored programmatic interventions should be developed to improve immunization coverage among those children and mothers who are at highest risk of being under-immunized or not immunized.